UTILIZATION OF SENTINEL-2 IMAGES FOR MAPPING THE CORAL REEF AREA IN THE CONSERVATION AREA OF PIEH ISLAND WATERS 2022 - Amatullah, Ulfi Rahmi; Febriandi, Febriandi; Ernawati, Ernawati; Arif, Dian Adhetya (International Remote Sensing Applied Journal, 2024)
Coral reefs are known as complex and productive shallow tropical marine ecosystems. They serve as a habitat for various species of marine plants, marine animals, and marine microorganisms. The deterioration of coral reefs threatens the survival of this shallow marine ecosystem. Mapping the distribution of coral reefs using remote sensing technology is a crucial instrument in the effort to monitor and protect coral reefs while preserving the marine environment. This research aims to map and measure the extent of coral reefs in the Pieh Islands Marine Conservation Area in 2022. In this study, we used Sentinel-2 imagery from 2022 and applied the Object-Based Image Analysis (OBIA) method to detect the extent of coral reefs. Sentinel-2 imagery was processed using ArcGIS and eCognition software, involving atmospheric correction, image clipping, image compositing, segmentation, image classification, and accuracy testing. The data processing results indicate that coral reefs are distributed around the waters of Pieh Islands, with the highest density located to the south of Pieh Islands's waters. The total extent of detected coral reefs in this study is 15.76 hectares. The use of Sentinel-2 imagery with the OBIA method has proven to be effective in detecting the extent of coral reefs in the Pieh Islands Marine Conservation Area.